2015
DOI: 10.1016/j.burn.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The mediating relationship of self-awareness on supervisor burnout and workgroup Civility & Psychological Safety: A multilevel path analysis

Abstract: a b s t r a c tThe purpose of this study was to examine whether managerial self-awareness (defined as degree of agreement between self and subordinate ratings of leaders' behaviors) mediates the relationship between supervisor burnout and supervised workgroup climate. Using an HLM approach, supervisor emotional exhaustion, depersonalization and personal accomplishment exhibited significant indirect relationships with workplace Civility and Psychological Safety, via managerial self-awareness. No direct relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 69 publications
(58 reference statements)
4
25
0
3
Order By: Relevance
“…Some previous research findings related with Turkish teachers are coherence with the results of the current study that teachers experience some degree of psychological unsafety. When we count on the result suggesting "psychological safety is an important aspect of workplace climate" (Hernandez et al, 2015) we can relate the current results to the results of school culture, school climate and professional well-being. For instance, Yaman and Güngör (2014) found that teachers had a low level of exclusion bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous research findings related with Turkish teachers are coherence with the results of the current study that teachers experience some degree of psychological unsafety. When we count on the result suggesting "psychological safety is an important aspect of workplace climate" (Hernandez et al, 2015) we can relate the current results to the results of school culture, school climate and professional well-being. For instance, Yaman and Güngör (2014) found that teachers had a low level of exclusion bias.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, psychological unsafety indicates more conflict and less team satisfaction among group members. Thus, it is an important aspect of workplace climate (Hernandez, Luthanen, Ramsel and Osatuke, 2015). Workplace climate is a basic condition for psychological safety.…”
Section: Introducationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on psychological un/safety include items as: "It's easy to speak up anything on your mind" Garvin et al, 2008), "I am not afraid to express my opinions here" (Lyu, 2016), "People, here, can bring up problems and difficult situations and don't hesitate to take risks" (Hernandez et al, 2015), "If you make a mistake here it is held against you afterwards" (Edmondson et al, 2004). "Institutional Psychological Unsafety Scale" which was developed and its validity and reliability analysis conducted by Yıldırım and Yenipınar (2017) was used.…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…As for "Psychological unsafety", it is that for employee, considering Employees who work in organizations in which psychological unsafety faced intensively are inclined to blame others for mistakes, problems and failures (Carmeli and Gittell, 2008). This situation threats also positive work environment, organisational learning and employees in displaying their potentials for organisational development (Carmeli and Gittell, 2008;Hernandez, Luthanen, Ramsel and Osatuke, 2015). Mistakes, failures are tools of learning and development in organisational learning (Garvin, Edmondson and Gino, 2008;Kahn, 2007).…”
Section: Introductionmentioning
confidence: 99%